The History Reflected in Colors (Eurasian Scientific Herald, 2024)
This article describes the life and creative path of Vasily Ivanovich Surikov, one of the brilliantly talented Russian artists who created effectively in the historical genre and made a great contribution to the development of the Russian art school, as well as a collection of perfectly crafted compositions and human figures in the artist's works. skillful ability; fine sense of colors and well-thought-out coloring of pictures; referring to Russian history, the main features of the art of re-creating historical situations are discussed